Role of Legislature in Sustainable Agricultural Development in Developing Nations: A Case Study of Nigeria - Akinbode Michael Okunola (Turkish Journal of Agriculture: Food Science and Technology)
When continuity is lacked in the agricultural programs and policies of a developing nation, such nation cannot avoid to keep moving round a circle. Such nation’s agricultural sector will be full of activities without actions and achievements will elude such country. This study therefore reviewed some of the agricultural programs and policies in Nigeria, their failures and successes as well as reasons behind the failures and success vis-à-vis the recent agricultural development strategy of Nigeria; Agricultural Transformation Agenda which has had its attending major successes of lifting the agricultural economy of Nigeria from being a democratic dividend to profit-oriented commercial business sector of the economy and x-rayed the role of legislature in sustainability of the successes of the agricultural strategy for continuity of agricultural development in Nigeria.